Tourist attitude towards performing arts heritage: case study of Cantonese opera in China - Jian Ming Luo; Chon Fai Kou; Jian Yang (Cogent Social Sciences)
Cultural heritage tourism is a significant and rapidly growing tourism. Cantonese opera, as a vital element of the cultural heritage in the Greater Bay Area (GBA), faces the challenge of preserving its relevance amidst rapid urbanisation and globalisation. Despite its cultural importance, research on tourists’ attitudes towards performing arts heritage, particularly Cantonese opera, still needs to be expanded, creating a gap in understanding how these cultural products can be more effectively managed and promoted. To address this gap, a scale was developed to measure tourist’s attitudes toward Cantonese opera in the GBA, China. A mixed-methods approach was employed, starting with qualitative interviews, followed by quantitative surveys to validate the scale. The results show that tourist attitude is operationalised by the following dimensions: perceived benefits, cultural value, composition elements, virtuosity, immediate feelings, evaluation emotion, past participation and behavioural intention. The findings offer valuable insights for policymakers and cultural managers in the GBA, providing practical recommendations to enhance the promotion and preservation of this unique cultural asset. This scale also serves as a tool for destination managers to promote cultural products to tourists better and strengthen their competitive edge.